2014
DOI: 10.1002/jcb.24960
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective Effects of Viral Overexpression of microRNA-22 in Rat and Cell Models of Cerebral Ischemia-Reperfusion Injury

Abstract: Several studies have reported that microRNA (MIR) is involved in the pathogenesis and progression of ischemic diseases, including cerebral ischemia, and that MIR-22 may inhibit the inflammatory response and cell apoptosis, which contribute to ischemia/reperfusion (I/R) injury. However, the specific function of MIR-22 in cerebral I/R injury remains far from clear. This study aimed to examine the potential protective effect of MIR-22 against cerebral I/R injury and its mechanism. As predicted, adenovirus-mediate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
49
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(53 citation statements)
references
References 33 publications
3
49
0
1
Order By: Relevance
“…Within the nervous system, the miR-22 family has been reported to participate in neuroprotection (Yu et al, 2015; Jovicic et al, 2013), neurodegeneration (Lee et al, 2011), neuroinflammation (Parisi et al, 2013; Siegel et al, 2012), neurodevelopment (Volvert et al, 2014; Berenguer et al, 2013), and neuroplasticity (Chen et al, 2013). Thus, although this family appears to have multiple roles in the nervous system and disease, our current studies identify members of this family as specifically involved in the suppression of memory formation.…”
Section: Discussionmentioning
confidence: 99%
“…Within the nervous system, the miR-22 family has been reported to participate in neuroprotection (Yu et al, 2015; Jovicic et al, 2013), neurodegeneration (Lee et al, 2011), neuroinflammation (Parisi et al, 2013; Siegel et al, 2012), neurodevelopment (Volvert et al, 2014; Berenguer et al, 2013), and neuroplasticity (Chen et al, 2013). Thus, although this family appears to have multiple roles in the nervous system and disease, our current studies identify members of this family as specifically involved in the suppression of memory formation.…”
Section: Discussionmentioning
confidence: 99%
“…The finding that loss of miR-22 results in an accelerated epileptogenesis suggests delivery or over-expression of miR-22 might be a potential therapeutic strategy. This could be achieved using miRNA mimics, synthetic double-stranded molecules or other approaches [17,18]. Notably, intracerebral injection of mimics for miR-22 and other inflammationlinked miRNAs has been reported to reduce seizures in the present model [16,36].…”
Section: Discussionmentioning
confidence: 84%
“…Another study found that after myocardial ischemia, over-expression of microRNA-1 can promote cardiomyocyte apoptosis, with the mechanism of inhibiting anti-apoptotic gene Bcl-2, IGF-1 expression and inducing cells into the process of apoptosis. Over-expression of microRNA-21 can reduce cell apoptosis, and its mechanism is to interfere with the activity of PDCD4 and AP-1, inhibit the ac- [19].…”
Section: Discussionmentioning
confidence: 99%